2017
DOI: 10.2174/1574892812666170727154643
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Space of FLT3 Inhibitors as Potential Anti-AML Drugs

Abstract: Although some of those compounds expressed potent bioactivities and have reached the advanced clinical trials for the treatment of leukemia, there are still several problems need to be faced before they enter the market eventually, especially the drug resistance issue. The improvement of therapeutic potency for FLT3 inhibitors might depend on the useful combination therapy and further refinement of the intrinsic properties of FLT3 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…9–11 Subsequently, a large number of FLT3 inhibitors (FLT3i) have been exploited for the treatment of AML, in response to the high correlation between FLT3 and AML. 12 The first-generation FLT3i were multitarget and nonselective inhibitors, including midostaurin, 9 which possibly caused off-target side effects. The second-generation FLT3i had better specificity and less toxicity, such as gilteritinib 13 and quizartinib 14 (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9–11 Subsequently, a large number of FLT3 inhibitors (FLT3i) have been exploited for the treatment of AML, in response to the high correlation between FLT3 and AML. 12 The first-generation FLT3i were multitarget and nonselective inhibitors, including midostaurin, 9 which possibly caused off-target side effects. The second-generation FLT3i had better specificity and less toxicity, such as gilteritinib 13 and quizartinib 14 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…6-Bromo-1-(cyclopropylsulfonyl)-1,2,3,4-tetrahydroquinoline (11) Yellowish oil; yield: 44%; 1 H NMR (500 MHz, DMSO-d 6 ) δ 7.49 (d, J = 8.5 Hz, Ar-H, 1H), 7.39 (d, J = 2.5 Hz, Ar-H, 1H), 7.32 (dd, J = 8.5, 2.0 Hz, Ar-H, 1H), 3.70-3.68 (m, CH 2 , 2H), 2.83 (t, J = 7.0 Hz, CH 2 , 2H), 2.77-2.72 (m, CH, 1H), 1.98-1.93 (m, CH 2 , 2H), 0.97-0.92 (m, CH 2 × 2, 4H); LC-MS (ESI †): m/z calcd. for C 12 H 14 BrNO 2 S: 314.99 [M + H] + ; found: 317.13, 319.13.6-Bromo-1-(phenylsulfonyl)-1,2,3,4-tetrahydroquinoline(12) White solid; yield: 51%; 1 H NMR (500 MHz, DMSO-d 6 ) δ 7. 1H), 5H), 7.38 (dd, J = 9.0, 2.5 Hz, 1H), 1H), (m, CH 2 , 2H), 2.44-2.39 (m, CH 2 , 2H), 1.60-1.51 (m, CH 2 , 2H); LC-MS (ESI): m/z calcd.…”
mentioning
confidence: 99%
“…It has been reported that AML is the most common cause of leukemia-related mortality in adult patients with a 5-year overall survival (OS) around 40% 3. Despite the use of new target drugs such as FLT3 inhibitors and IDH1/2 inhibitors in the clinic, the mainstay of treatment approach is chemotherapy and several chemotherapeutic drugs including anthracycline are predominantly used 46. Although great prognostic improvement of AML has been made during the past few decades, 60–80% of patients who have initially achieved complete remission finally relapse while parts of them eventually die of this disease due to chemoresistance 7.…”
Section: Introductionmentioning
confidence: 99%